MOSQUE-BASED ECONOMIC EMPOWERMENT IN THE MALAY WORLD: Views of Ibnu Khaldun's Asabiyah and Malik Bennabi's Civilization Theories - Rizqi Anfanni Fahmi; Suyitno Suyitno; Endang Rochmiatun (Al-Qalam, 2023)
In the Malay world, mosque-based economic empowerment has grown in popularity, with Indonesia and Malaysia dominating the presentation of documents on the mosque economy. The purpose of this study was to conduct a literature review on the economic empowerment of mosques in the Malay world and its relationship to civilization. On the basis of keywords pertinent to the economic empowerment of mosques in the Malay world, scholarly articles indexed by Scopus and Google Scholar were reviewed. Using techniques of content analysis, 44 relevant articles were gathered and analyzed. The results indicated that mosque-based economic empowerment programs have increased in Indonesia, Malaysia, and Singapore, but not in Southern Thailand, Brunei Darussalam, or the Philippines, where mosques continue to be centers of religious activity. Mosque-based economic empowerment is consistent with Ibn Khaldun's Asabiyah concept, in which the mosque serves as a social organization for Muslims in Malay countries. In some countries, mosque-based economic empowerment has reached a spiritual and rational stage, according to Malik Bennabi. This study can be used as a resource by administrators of mosques and Islamic organizations in the Malay world region to promote economic empowerment to strengthen social cohesion and the Asabiyah of the Malay Muslim community.